Google Play : Millennials’ online experience & Behavioral concepts - Heřman, Jiří; Lhotáková, Markéta, 1971-; Grygarová, Pavla; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
This thesis aims to obtain a better understanding of Millennials’ experience on Google Play platform with the help of behavioral concepts. It collects current knowledge in the field of online experience and online marketing concepts, which are then combined with a classical marketing mix (4Ps) and behavioral theories, to form a theoretical system which underpins the practical research.The topic is then explored by a secondary quantitative research and a primary qualitative research. The secondary quantitative research collects the information about global and Czech Millennials and their relationship to digital world. The primary qualitative research is based on Google Play usability testing and in-depth interviews. The results show that Czech Millennials are prepared to consume online content, but they do not consume more Google Play paid content because of the suboptimal consumer experience, social barriers and insufficient communication of the content value. Recommendations addressing the barriers and opportunities to drive the Millennials’ consumption of paid content were formulated based on the research findings and behavioral concepts.
Vedoucí práce: Markéta Lhotáková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses